International Review of Management and Marketing, 2016, 6(S6) 180-184. Special Issue on "Management of Systems of Socio-Economic and Legal Relations in Modern Conditions of Development of Education and Society” - Anait S. Basyuk; Alexander Yu. Anisimov; Victoria V. Prokhorova; Oksana N. Kolomyts; Fedor V. Shutilov (International Review of Management and Marketing, 2016)
The key point in the management of modern industrial innovation cluster in the global economic market, as well as on the inside of the domestic arena, is administration, responsible for making decisions in the production process, management policy, the sale of products on the market. Most established and functioning innovation clusters in Russia were created on the initiative of the regional authorities and the main role of the management company’s innovation cluster usually performs one of the “universal institutions of development” of the region. The formation and operation of cluster management in the management focuses on enhancing interaction of all participants in the cluster, in order to implement all the main objectives of development of innovation clusters and implement joint projects, to represent the interests of residents in the cluster bodies, development institutions, in the arena of domestic and global economic market. In the process of writing a new approach to the management of management of innovation clusters, based on the representation of system activity, allowing, on the one hand, to bring a progressive dynamism of the cluster and its objectives, on the other hand, it ensures high competitiveness both in domestic markets and in the world.